Currículo, tecnologias e alfabetização científica: uma análise da contribuição da robótica na formação de professores - Stroeymeyte, Tatiana Souza da Luz (2015)
This work fits into the line of research new technologies in education of the Post-graduate education: curriculum of the Catholic University of Sao Paulo. Aims to investigate the relationship between the Science Curriculum of São Paulo Nature and themes of technologies (educational robotics) to propose a teacher training program focusing on investigative education and the development of scientific literacy to understand the integrated educational robotics to the Natural Sciences curriculum applied in the final years of primary education can contribute to the development of Scientific Literacy Research has a qualitative approach and investigate the integration of Digital Technologies Information and Communication to the curriculum through a literature search and documentary and a field research with teachers who work with robotics applied to the teaching of science in schools belonging to the project Full Time School of the São Paulo public network's main theoretical actors, Gimeno Sacristán, Antonio Cachapuz, Philippe Perrenoud and taking as reference the principles of Freire's theory. The main results of this study were: the construction of an array that articulates the application areas of robotics with the thematic axes of the science curriculum and building continuing education program for teachers of the final years of elementary school. It concludes that robotics has a great potential for the development of Scientific Literacy. It has potential for the development of education for research, for the development of an emancipatory education in which the individual is aware of his changing role and application of the scientific method serving as a proxy of the classroom with scientific research